Industrial Relations: A Paradigmatic Analysis - Young, Stanley (Relations industrielles / Industrial Relations, 1982)
After noting some of the differences between paradigmatic and normal research, the author suggests, as has occurred with other disciplines, the need for industrial relations paradigmatic research.